Amyloid-β modulates the phase separation and aggregation of α-synuclein - Alexander Röntgen; Zenon Toprakcioglu; Owen M. Morris; Michele Vendruscolo (Proceedings of the National Academy of Sciences, 2025)
The aggregation of amyloid-β (Aβ) and α-synuclein (αSyn) into insoluble proteinaceous deposits is a hallmark of Alzheimer’s and Parkinson’s diseases. Recent evidence suggests that these amyloidogenic proteins act in synergy, with their coaggregation frequently observed in these disorders. In this study, we investigate the interaction of Aβ and αSyn using various biophysical tools. In particular, we explore the cocondensation of Aβ with αSyn, elucidating the pathways through which Aβ modulates αSyn phase separation. We studied different variants of Aβ, focusing on the most prominent species, namely Aβ42 and Aβ40. We found that Aβ42 and Aβ40 have fundamentally different mechanistic effects on the kinetics of αSyn condensation. Aβ42 initially forms large aggregates that act as heterogeneous nucleation sites which initiate the phase separation of αSyn. In contrast, Aβ40 is sequestered into αSyn condensates where it accelerates the liquid-to-solid transition of αSyn into amyloid aggregates. All other Aβ variants we probed fell into one of these two mechanistic pathways, with Aβ37, Aβ39, and Aβ35-25 exhibiting similar behavior to Aβ40, whereas Aβ43 triggered nucleation processes similar to Aβ42. Given the complexity behind amyloid formation, it is key to understand how molecular partners can interact with one another. Our results thus illustrate the extreme sensitivity of protein mixtures and shed light on some of the mechanisms involved in the cocondensation and aggregation of Aβ with αSyn.